A fé desmitificada: representações da religião católica no romance a Cocanha, de José Clemente Pozenato - Roy, Valeria Acosta (My University, 2019)
Taking the novel A cocanha (2000), by José Clemente Pozenato as our corpus, this research aims to demonstrate the demystification process of the Catholic religion present in the context of Italian immigration at the end of the XIX century in the Northeast region of Rio Grande do Sul, Brazil. Contrary to other predominant historiographic and literary narratives that exalt the religion of the Italian immigrants, and that in many cases is even considered responsible for the success of the colonization, the fiction narrative of Pozenato offers alternative versions of the History presenting a Catholic religion demystified. In order to reach that objective, an interdisciplinary theoretical foundation is employed that includes the fields of History, Theology and Philosophy. This historical survey assists in the understanding of the context in which the characters are inserted, as well as the identification of past events that in different ways contributed to the mystification of the Catholic religion. The theological foundation offers key elements to understand components of the catholic doctrine and how it subsequently affects the behavior of their followers. In the field of philosophy, the concept of “myth” of Mircea Eliade is used to understand the mystification and the demystification process present in the novel, as well as the concept of “suffering” of Ludwig Feuerbach as another important factor that deconstruct the religion of the Italian immigrants.
Tomando como corpus o romance A cocanha (2000), de José Clemente Pozenato, este trabalho objetiva demonstrar o processo de desmitificação da religião católica presente na obra no contexto da imigração italiana do final do século XIX, na região Nordeste do Rio Grande do Sul, Brasil. Observa-se que, contrário a alguns discursos historiográficos e literários predominantes que enaltecem a religião dos imigrantes, e que em muitos casos a consideram responsável pelo sucesso da colonização, a narrativa ficcional de Pozenato traz versões alternativas da História, apresentando uma religião católica questionada. Para atingir esse objetivo recorre-se a um embasamento teórico interdisciplinar que abrange a história, a teologia e a filosofia. O levantamento histórico auxilia no entendimento do contexto no qual os personagens estão inseridos, assim como na identificação dos acontecimentos passados que de diferentes maneiras contribuíram para a mitificação da religião católica. O embasamento teológico oferece elementos-chave para entender a doutrina católica e seus efeitos na conduta de seus seguidores. No campo filosófico, utiliza-se o conceito de mito de Mircea Eliade para entender o processo de mitificação e desmitificação presentes no romance, assim como o conceito de sofrimento de Ludwig Feuerbach como outro fator importante que desconstrói a religião dos colonos imigrantes.
Keywords: Pozenato, José Clemente, $d 1938-; Catolicismo; Emigração e imigração na literatura; Italianos; Mito; Catholicism; Emigration and immigration in literature; Italians; Myth